Emergency Removal of a Proximal Tracheal Foreign Body by Tracheotomy in a Dog and a Cat - Teruo Itoh; Atsuko Kojimoto; Hiroki Shii (Case Reports in Veterinary Medicine)
There have been few reports of emergency cases of proximal tracheal foreign bodies in dogs and cats. Here, we report a dog and a cat that underwent an emergency tracheotomy for a foreign body in the proximal trachea. Case 1 was a dog with respiratory arrest caused by a large stone in the proximal trachea. The stone was immediately removed via tracheotomy without anesthesia. After intubation and ventilation under anesthesia, hypoxia persisted but improved after aspiration of 100 mL of bloody fluid from the lower trachea. Case 2 was a cat with dyspnea because of a proximal tracheal stone and increased radiopacity in the right lung. The stone was removed via tracheotomy after mask induction of anesthesia, followed by intubation and incision closure. Radiographs immediately after extubation showed worsened right lung atelectasis, alleviated by reintubation and positive pressure ventilation. Both patients recovered completely after surgery. An emergency tracheotomy may be indicated for a large foreign body in the proximal trachea. Additionally, concurrent conditions in the lower respiratory tract should be addressed.